Efficient synthesis and RAFT polymerization of the previously elusive N‐[(cycloalkylamino)methyl]acrylamide monomer class. Issue 13 (25th April 2017) - Chalmers, Benjamin A.; Alzahrani, Abdullah; Hawkins, Gerard; Aldabbagh, Fawaz
Abstract : Schiff base salts allowed the multigram preparation of methylene amino substituted acrylamide monomers. These, as well as the hydrochloride salt intermediates, were subjected to controlled/living polymerizations for the first time. One‐pot sequential reversible addition‐fragmentation chain transfer (RAFT) polymerizations resulted in well‐defined di‐ and triblock copolymers.